Why a Focus on Sporting Tests Would Reveal an Alternate Story and Raise Ethical Questions about Agon: A Commentary - Kretchmar R. Scott (Sciendo, 2019)
Loy and Morford focus on "agon" as an important window through which to understand human life and development. Competition in war and sport was culturally significant then, and it is culturally significant today, albeit in modified forms. In this commentary, I attempt to do two things - first, identify implications of some conceptual distinctions, and second, point out normative questions raised by the Loy/Morford analysis. I find it worthwhile to differentiate clearly between tests and contests. If the historical and sociocultural spotlight were turned on sporting "tests" rather than "contests", that is, on trying to solve physically demanding problems well rather than trying to solve them better than at least one other party, then another story than the agonal account could be told. War would probably no longer serve as the best historical and prehistorical analogue for sport. Rather, it might be hunting. I add, that, on one hand, competitive sport is far less violent and, therefore, far more defensible today than it was previously. On the other hand, joy in playing is often sacrificed on the altar of any number of extrinsic rewards. Success, even gained by questionable means, replaces skill-based and virtue-generated achievement. This threatens the connection endorsed by MacIntyre between practices and virtues.